Urgensi Komunikasi dalam Pengembangan Organisasi Modern - Fabianus Fensi (Ultimacomm: Jurnal Ilmu Komunikasi, 2017)
Modern organization requires a participatory model of communication which provides the room for the involvement of all organizational components. Role hierarchy is required, but it aims to smoothen the flow of information distribution within the organization. Weak standards of organizational communication often cause conflict in an organization. Conflicts can occur between members and organizations, between members within the organization, or between organizations and members. Therefore, conflict resolution mechanisms that win the common interest are needed. Superiors and subordinates are the organizational devices of the channeling or communications actors within the organization so that the organization mechanism runs according to mutual agreement within the organization. No conflicts have no way out. The importance for an organization is to negotiate egalitarian to win the common interest as the vision and mission of the organization. Keywords: Conflict, communication, negotiation, organization